Geometric Constraints and the Anatomical Interpretation of Twisted Plant Organ Phenotypes - Weizbauer, Renate; Peters, Winfried S.; Schulz, Burkhard (Frontiers in Plant Science, 2011)
The study of plant mutants with twisting growth in axial organs, which normally grow straight in the wild type, is expected to improve our understanding of the interplay among microtubules, cellulose biosynthesis, cell wall structure, and organ biomechanics that control organ growth and morphogenesis. However, geometric constraints based on symplastic growth and the consequences of these geometric constraints concerning interpretations of twisted organ phenotypes are currently underestimated. Symplastic growth, a fundamental concept in plant developmental biology is characterized by coordinated growth of adjacent cells based on their connectivity through cell walls. This growth behavior implies that in twisting axial organs, all cell files rotate in phase around the organ axis, as has been illustrated for the Arabidopsis spr1 and twd1 mutants in this work. Evaluating the geometry of such organs, we demonstrate that a radial gradient in cell elongation and changes in cellular growth anisotropy must occur in twisting organs out of geometric necessity alone. In-phase rotation of the different cell layers results in a decrease of length and angle towards organ axis from the outer cell layers inwards. Additionally, the circumference of each cell layer increases in twisting organs, which requires compensation through radial expansion or an adjustment of cell number. Therefore, differential cell elongation and growth anisotropy cannot serve as arguments for or against specific hypotheses regarding the molecular cause of twisting growth. We suggest instead, that based on mathematical modelling, geometric constraints in twisting organs are indispensable for the explanation of the causal connection of molecular and biomechanical processes in twisting as well as normal organs.